Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, dan Inflasi terhadap Kemiskinan di Kota Banjarmasin Tahun 2007-2018 - Ellisa Dewi Norsita Fahjarini; Eny Fahraty (PPJP ULM, 2020)
This study was conducted to determine: (1) The Effect of economic growth onpoverty in Banjarmasin City, (2) The number of population in poverty in BanjarmasinCity, (3) the Effect of inflation on poverty in Banjarmasin City.This type of research is quantitative research with the method used that is usingmultiple linear regression methods. The variables used are poverty, economic growth,population, and inflation. While the data used to analyze this research uses time-seriesdata by using secondary data that are data sources that do not directly provide data todata collectors, such as data from the Central Statistics Agency (CSA) BanjarmasinCity.The results showed the variables of economic growth, population, and inflationtogether affected poverty, and economic growth factors dominantly influenced povertyin the city of Banjarmasin in 2007-2018.